Metabolites Identification of Chemical Constituents From the Eggplant (Solanum melongena L.) Calyx in Rats by UPLC/ESI/qTOF-MS Analysis and Their Cytotoxic Activities - Song, Yuanyuan; Mei, Ting; Liu, Yan; Kong, Shengnan; Zhang, Jincheng; Xie, Minzhen; Ou, Shan; Liang, Meixia; Wang, Qi (Frontiers in Pharmacology, 2021)
Eggplant (Solanum melongena L.) Calyx is a medicinal and edible traditional Chinese medicine with anti-inflammatory, anti-oxidant, and anti-cancer properties. However, the pharmacodynamic components and metabolic characteristics remain unclear. Amide and phenylpropanoid were the two main constituents, and four amides, including n-trans-p-coumaroyltyramine (1), n-trans-p-coumaroyloctopamine (2), n-trans-p-coumaroylnoradrenline (3), n-trans-feruloyloctopamine (4), and a phenylpropanoid neochlorogenic acid (5) were selected. In this study, these five representative compounds showed cytotoxic activities on A549, HCT116, and MCF7 cells. In addition, the metabolites of 1-5 from the eggplant calyx in rats were identified. In total, 23, 37, 29, and 17 metabolites were characterized in rat plasma, urine, feces, and livers, respectively, by UPLC/ESI/qTOF-MS analysis. The metabolism of amides and phenylpropanoid was mainly involved in hydroxylation, methylation, glucuronidation, or sulfation reactions. Two hydroxylated metabolites (1-M2 and 2-M3) were clearly identified by comparison with reference standards. Rat liver microsome incubation experiments indicated that P450 enzymes could hydroxylate 1-5, and the methylation reaction of the 7-hydroxyl was also observed. This is the first study on the in vivo metabolism of these compounds, which lays a foundation for follow-up studies on pharmacodynamic evaluations and mechanisms.